Teacher's Efforts to Increase the Learning Motivation of Class Ix Students of Mts Sunan Pandanaran through Group Guidance Services in Guidance and Counseling - Fany Rifqoh (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2024)
The problem in this research is the lack of student interest or motivation to learn in class. This can be seen from the lack of motivation of students because they do not think that without the National Examination (UN) they can be accepted at the school they hope for. These problems require solutions and must be solved immediately, these problems greatly influence learning activities and the achievement of learning objectives. In line with this. This research will try to solve the problems that occur through Classroom Action Research (PTK) so that problems related to student learning motivation can be solved. This research is included in the type of action research with the Mc model. Taggart. This research consists of two cycles. Each cycle consists of four stages, namely planning, implementing actions, observing and reflecting. Data collection techniques, namely observation, questionnaires, interviews and documentation of learning activities. Observations were carried out to determine initial conditions related to the learning motivation of class IX MTs Sunan Pandanaran students, questionnaires were used to evaluate each PTK activity carried out, interviews and documentation were used to obtain further statements, related to group guidance that had been carried out by class IX MTs students Sunan Pandanaran. Analysis was carried out using qualitative descriptive techniques supported by quantitative data. This research produced the following findings; (1) Class IX students' learning activities, especially in increasing students' learning motivation at MTs Sunan Pandanaran before being given group guidance services, obtained a score of 63.88% in the sufficient category, these results need to be improved through the second meeting in the first cycle. After observation and analysis, the second meeting resulted in an increase in score from initially 63.88% to 67.00%.